Political Crisis and Societal Governance:How Media Can be Societal Media? - TAKAHASHI, Toru (Journal of Sociocybernetics, 2016)
Political frustration of the people often comes along with protest movements on the streets. The street democracy becomes most powerful when the political system loses the people’s systemic trust. Therefore, we can see the street democracy as a symptom of the systemic political crisis. We have to be vigilant for political adventurism that exploits the people’s discontent. However, considering the chronic fiscal deficits of governments, we cannot rely only on governments. We have to expand our view beyond politics and governments. We are facing various problems at local, national and global level. It is necessary to develop societal governance that mobilizes and organizes multi-functional resources to cope with the multi-level challenges. As J.N. Rosenau formulates, governance is an encompassing phenomenon that embraces governmental and non-governmental mechanisms. This paper reformulates the comprehensiveness of societal governance as multi-functionality and multi-levelness. It means that societal governance is an ecosystem of collaborative efforts that mobilizes multi-functional resources to cope with public problems across local, national and global levels. Innovations in media (especially, in the Internet) can contribute to creating fertile conditions for the efforts by advocating issues and connecting actors and resources. Media can make another step to a next stage of the development as liaison media in societal governance. Now we are witnessing the next step of the media’s development towards “societal media”.Political frustration of the people often comes along with protest movements on the streets. The street democracy becomes most powerful when the political system loses the people’s systemic trust. Therefore, we can see the street democracy as a symptom of the systemic political crisis. We have to be vigilant for political adventurism that exploits the people’s discontent. However, considering the chronic fiscal deficits of governments, we cannot rely only on governments. We have to expand our view beyond politics and governments. We are facing various problems at local, national and global level. It is necessary to develop societal governance that mobilizes and organizes multi-functional resources to cope with the multi-level challenges. As J.N. Rosenau formulates, governance is an encompassing phenomenon that embraces governmental and non-governmental mechanisms. This paper reformulates the comprehensiveness of societal governance as multi-functionality and multi-levelness. It means that societal governance is an ecosystem of collaborative efforts that mobilizes multi-functional resources to cope with public problems across local, national and global levels. Innovations in media (especially, in the Internet) can contribute to creating fertile conditions for the efforts by advocating issues and connecting actors and resources. Media can make another step to a next stage of the development as liaison media in societal governance. Now we are witnessing the next step of the media’s development towards “societal media”.